Strategi Pengembangan Agribisnis Kopi Untuk Mendukung Wisata Telaga Ngebel Ponorogo - Mila Diana Sari (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2020)
Abstract— One of the natural attractions in Ponorogo is Ngebel lake. Increasing the tourist attraction of Ngebel Lake can be done by developing agribusiness around it. The coffee agribusiness in the Ngebel Lake area was developed traditionally so that it has not been able to support the development of the Ngebel Lake tourism park. On the other hand, to increase the attractiveness of a tourist park, it is necessary to support the management of the potential of the surrounding area. Therefore it is necessary to conduct a study on the strategy of developing coffee agribusiness so that the attractiveness of Lake Ngebel can be increased. The method used in this study is to analyze the potential of coffee agribusiness using a SWOT analysis so that the most strategic method in developing coffee agribusiness can be determined. The results showed that the coffee agribusiness in Gondowido Village could support Ngebel Lake agro-tourism through improving weaknesses by taking advantage of opportunities. Keywords—: Strategy; coffee agribusiness; Ngebel lake.